2013
DOI: 10.1539/joh.13-0055-fs
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Airborne Bacteria in Railway Stations in Tokyo, Japan

Abstract: Distribution of Airborne Bacteria in Railway Stations in Tokyo, Japan: Tamami KAWASAKI, et al. Biotechnology Laboratory, Railway Technical Research Institute— Objectives We performed the current study to (1) understand the distribution of culturable airborne bacteria over a one‐year monitoring period, (2) confirm places in stations where airborne bacteria are highly detected, (3) understand the factors that affect concentrations of airborne bacteria and (4) compare the distributions of airborne bacteria and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…People also bring their overclothes, which may contribute to the increased amount and diversity of microorganisms in this part of the cinema. A similar observation was provided by Kawasaki et al (2013). They detected a high number of airborne bacteria in a railway station and it was especially high in summer.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…People also bring their overclothes, which may contribute to the increased amount and diversity of microorganisms in this part of the cinema. A similar observation was provided by Kawasaki et al (2013). They detected a high number of airborne bacteria in a railway station and it was especially high in summer.…”
Section: Discussionsupporting
confidence: 81%
“…They detected a high number of airborne bacteria in a railway station and it was especially high in summer. They concluded that the number of railway customers, not humidity, was the main factor affecting the concentrations of bacteria [29]. The next exanimed building of public interest was a pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this observation can be applied and generalized to bacteria in aerosols and to those of different indoor environments is unknown. Nonetheless, one should use caution in such generalizations and comparisons, as environmental effects such as temperature and humidity on microbial community assemblages are likely to be influenced by sample locations, method of sampling, and the microbial members and communities in question (17,59,60). When outlier samples based on their high taxonomic diversity were removed, the effects of temperature and humidity on MTR ␣-diversity no longer were significant.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the microbiological contents of the aerosol in this unique built environment are relatively unknown. The majority of current microbiological assessments of subway networks had been limited to conventional culture methods (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) or limited culture-independent methods (18,19), which are likely to underestimate the true spectrum of microorganisms present. Culture-based studies are also inherently restrictive in the comparison of microbial communities between samples, as the organisms cultivated for analysis are dependent on the selective growth conditions chosen.…”
mentioning
confidence: 99%
See 1 more Smart Citation